Pelatihan Specimen Collection dan Pra-Analitik Covid-19 di Sekitar RSIA Al-Islam Bandung - Triyani, Yani; Puspita, Sara; Nilapsari, Rika; Noormartany, Noormartany (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The gold standard examination to make a diagnosis COVID-19 is an examination using the Nucleic Acid Amplification Test (NAAT) method, for example, Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). Current data shows that more than 60 percent of errors occur in the pre-analytic process. The purpose of this community service is to help improve the knowledge and abilities of health workers in the implementation of specimen collection, stages and impacts of pre-analytical errors, types of examinations for laboratory examinations enforcement of the Covid-19 diagnosis. The method of the service was online, in the form of lectures, video screenings and discussions, for the evaluation using pretest and posttest activities. The result of this service is that there is an increase in understanding and knowledge as well as insight into laboratory examination specimen collection pre-analytic activities. COVID-19.